Comprehensive Analysis of Intermittent Fasting on Anthropometric Indices, Glycemic Control, and Serum Insulin Levels in Obese Patients with Type 2 Diabetes - Aparnna Unnikrishnan Nair; Naveenkumar Nallathambi; S Yogesh; Lakshmi Murugesan; Harini B. Narayanan; Rajiv Ranjan; Nithila Sivakumar; Lakshiya Ramamoorthy; K Arun (Journal of Pharmacy and Bioallied Sciences, 2024)
Background: Type 2 diabetes significantly impacts socioeconomic conditions, with periods of obesity and insulin resistance preceding diagnosis. Fasting, practiced for millennia, offers the potential to manage and possibly reverse diabetes. This study aims to assess the effects of intermittent fasting on various health indicators in obese type 2 diabetic patients. Methodology: Thirty obese volunteers with type 2 diabetes mellitus, uncontrolled by metformin alone, aged 20-60, were included. They followed a 16:8 intermittent fasting regimen for four weeks. Initial and postintervention measurements included height, weight, BMI, waist-hip ratio, waist circumference, fasting blood sugar, and serum insulin. Results were compared using the student t-test. Results: After four weeks, significant reductions were observed in anthropometric indices and fasting blood sugar, but no change in serum insulin levels. Conclusion: A 16:8 intermittent fasting regimen significantly reduced fasting blood glucose levels and anthropometric indices in obese type 2 diabetes patients over four weeks, with no effect on serum insulin levels. Larger and longer-term studies are needed to explore long-term effects and mechanisms.